Treatment of childhood acute lymphoblastic leukemia in Jakarta: Result of modified Indonesian National Protocol 94 - Djajadiman Gatot; Endang Windiastuti (Paediatrica Indonesiana, 2006)
Background Before 1990, the survival rates of childhood acutelymphoblastic leukemia (ALL) patients remained low. In 1994, theHematology Oncology Working Group of the Indonesian PediatricAssociation constructed a national protocol based on standard in-ternational protocol. As the outcome was still not promising, in 1998the protocol was modified by introducing low dose MTX infusion forCNS prophylaxis.Objective To analyze the survival of pediatric ALL patient treated withthe modified protocol in Cipto Mangunkusumo Hospital, Jakarta.Methods A prospective study was carried out to all newly diag-nosed and relapsed children with ALL from January 1998 throughDecember 2004. Patients were stratified into standard risk group(SRG) and high risk group (HRG). HRG met with one of thesecriteria: WBC >50 000/Ã¬l, the presence of CNS involvement, medi-astinal mass, relapse, or L 3 morphology. After completing induc-tion therapy, all patients received low-dose MTX (LDMTX) infusion(500 mg/m 2 ), especially for those aged less than 3 years. If thepatient could not afford LDMTX, cranial irradiation (CRT) was given.Results There were 309 patients, consisted of 190 SRG and 119 HRGpatients. Male to female ratio was 1.8:1. Complete remission wasachieved in 86.3% SRG patients compared with 63.8% in HRG pa-tients (P<0.05). Event-free survival (EFS) rate in SRG and HRG were65.9% (95%CI 59.8; 71.9%) and 40.4% (95%CI 32.5; 48.4%), respec-tively. The overall survival (OS) rates in SRG was 81.2% (95%CI 76.3;86.2%) and in HRG was 56.0% (95%CI 47.8; 64.2%). The overall OSand EFS for both groups were 71.6% (95%CI 67.0; 76.2%) and 59.6%(95%CI 54.5; 64.7%), respectively. Failure of therapy was mostly dueto severe aplasia resulted in bleeding and severe infection. CNS re-lapse was rare in both groups, i.e. 3.1% in SRG and 0.8% in HRG.Conclusion Treatment of ALL using modified national protocol forSRG shows promising results. However, the outcome of HRG pa-tients is still inferior to those reported elsewhere. The use of low-dose MTX infusion can replace the role of cranial irradiation asCNS prophylaxis measure.